2021
DOI: 10.3390/ijms22041678
|View full text |Cite
|
Sign up to set email alerts
|

The GAUGAA Motif Is Responsible for the Binding between circSMARCA5 and SRSF1 and Related Downstream Effects on Glioblastoma Multiforme Cell Migration and Angiogenic Potential

Abstract: Circular RNAs (circRNAs) are a large class of RNAs with regulatory functions within cells. We recently showed that circSMARCA5 is a tumor suppressor in glioblastoma multiforme (GBM) and acts as a decoy for Serine and Arginine Rich Splicing Factor 1 (SRSF1) through six predicted binding sites (BSs). Here we characterized RNA motifs functionally involved in the interaction between circSMARCA5 and SRSF1. Three different circSMARCA5 molecules (Mut1, Mut2, Mut3), each mutated in two predicted SRSF1 BSs at once, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 66 publications
0
49
0
1
Order By: Relevance
“…To understand the NRF1 and SMAD4 protein-protein interaction more completely, an extensive analysis of each protein and/or structural biology studies will be required. Recently, Barbagallo, D et al and Broggi, G et al reported that the RNA-binding motif responsible for the interaction between Serine and Arginine Rich Splicing Factor 1 (SRSF1) and circSMARCCA5 (a 269-nucleotide-long circRNA) are coupled with increased amounts of total Vascular Endothelial Growth Factor A (VEGFA) mRNA secretion and the recommended use of SRSF1 as a diagnostic immunomarker in gliomas [34,35]. In the case of NRF1, it appears to be both a negative regulator and an interaction partner of SMAD4.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the NRF1 and SMAD4 protein-protein interaction more completely, an extensive analysis of each protein and/or structural biology studies will be required. Recently, Barbagallo, D et al and Broggi, G et al reported that the RNA-binding motif responsible for the interaction between Serine and Arginine Rich Splicing Factor 1 (SRSF1) and circSMARCCA5 (a 269-nucleotide-long circRNA) are coupled with increased amounts of total Vascular Endothelial Growth Factor A (VEGFA) mRNA secretion and the recommended use of SRSF1 as a diagnostic immunomarker in gliomas [34,35]. In the case of NRF1, it appears to be both a negative regulator and an interaction partner of SMAD4.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration was assayed through Oris™ Cell Migration Assay (Platypus Technologies, Madison, WI, USA), as previously described [ 27 ]. Briefly, 3.5 × 10 4 transfected cells/well were seeded in a 96-well migration plate with the stoppers placed.…”
Section: Methodsmentioning
confidence: 99%
“…( C ) Bar graph showing the mean ± standard deviation of the percentage (%) of NC or SRSF1-transfected U87MG cell migration. The percentage of cell migration has been calculated as previously reported [ 27 ]. * p -value < 0.05 ( n = 6, Student’s t -test vs. control).…”
Section: Figurementioning
confidence: 99%
“…Circular RNAs may be involved in the regulation of glioma cell proliferation, migration, and invasion. They may be also involved in glioma angiogenesis via miRNA-526b-3p/MMP2 pathway and RNA-binding proteins [ 254 , 255 ]. Circ-ATXN1 were significantly upregulated in glioma-associated endothelial cells in comparison with astrocyte-associated endothelial cells (AECs), whereas knockdown of circ-ATXN1 significantly inhibited endothelial cell viability, migration and tube formation [ 255 ].…”
Section: Neoangiogenesis In Glioma Developmentmentioning
confidence: 99%